2011
DOI: 10.1007/s00125-011-2261-y
|View full text |Cite
|
Sign up to set email alerts
|

A large multi-centre European study validates high-sensitivity C-reactive protein (hsCRP) as a clinical biomarker for the diagnosis of diabetes subtypes

Abstract: Aims/hypothesis An accurate molecular diagnosis of diabetes subtype confers clinical benefits; however, many individuals with monogenic diabetes remain undiagnosed.Biomarkers could help to prioritise patients for genetic investigation. We recently demonstrated that highsensitivity C-reactive protein (hsCRP) levels are lower in UK patients with hepatocyte nuclear factor 1 alpha Diabetologia (2011) 54:2801-2810 DOI 10.1007/s00125-011-2261 (HNF1A)-MODY than in other diabetes subtypes. In this large multi-centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 28 publications
(40 reference statements)
7
76
2
1
Order By: Relevance
“…This occurred in spite of a more favorable lipid profile and lower CRP levels in these patients. This seemingly antiatherogenic lipid profile and low CRP level in HNF1A mutation carriers have been described earlier (18,19). The antiatherogenic profile of HNF1-MODY seems to be also associated with low sCD36, the scavenger protein that was shown to play a substantial role in the pathogenesis of atherosclerosis (20).…”
Section: Discussionsupporting
confidence: 56%
“…This occurred in spite of a more favorable lipid profile and lower CRP levels in these patients. This seemingly antiatherogenic lipid profile and low CRP level in HNF1A mutation carriers have been described earlier (18,19). The antiatherogenic profile of HNF1-MODY seems to be also associated with low sCD36, the scavenger protein that was shown to play a substantial role in the pathogenesis of atherosclerosis (20).…”
Section: Discussionsupporting
confidence: 56%
“…Recently, a new biomarker for HNF1A, high-sensitivity Creactive protein, has been reported [15,27]. Presently, this biomarker is not in routine use in our registry.…”
Section: Discussionmentioning
confidence: 98%
“…Studies indicate that lower levels of the biomarker high-sensitivity C-reactive protein (hs-CRP) can predict HNF1A-MODY patients for diagnostic genetic testing [15].…”
Section: Introductionmentioning
confidence: 99%
“…We tested this theory initially in a small number of local patients with MODY 11 and then the results were replicated in two large European studies, 12,13 including nearly 700 cases of HNF1A-MODY. The results showed that levels of hsCRP were significantly lower in those with HNF1A mutations compared with those with all other forms of diabetes and also compared with those without diabetes.…”
Section: C-reactive Protein and Hnf1a-modymentioning
confidence: 99%